2014
DOI: 10.1590/s0080-623420140000100022
|View full text |Cite
|
Sign up to set email alerts
|

Duration of smoking cessation for the prevention of surgical wound healing complications

Abstract: The study aimed to find scientific evidence about the duration of preoperative smoking cessation required to reduce surgical wound healing complications. An integrative review was performed in the databases, Latin American and Caribbean Literature on Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE), from 08/17/2012 to 09/17/2012, using the keywords: tobacco use cessation and wound healing; tobacco use cessation and preoperative period; tobacco use cessation and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
4
1
1
Order By: Relevance
“…Strict knowledge of risk factors for surgical wound complications in breast and abdominal regions contributes to better systematization of care and planning of therapeutic strategies, including greater caution for certain types of surgery, as well as, chronic conditions, exposure to radiotherapy, instructional level and possible social vulnerability for people at productive age. Furthermore, although the present study did not identify an association between obesity and smoking, previous research has shown that weight reduction 13 and smoking cessation 37 favor the healing process of the wound. In this sense, care must be based on a holistic, patient-centered approach 13 .…”
Section: Discussioncontrasting
confidence: 98%
“…Strict knowledge of risk factors for surgical wound complications in breast and abdominal regions contributes to better systematization of care and planning of therapeutic strategies, including greater caution for certain types of surgery, as well as, chronic conditions, exposure to radiotherapy, instructional level and possible social vulnerability for people at productive age. Furthermore, although the present study did not identify an association between obesity and smoking, previous research has shown that weight reduction 13 and smoking cessation 37 favor the healing process of the wound. In this sense, care must be based on a holistic, patient-centered approach 13 .…”
Section: Discussioncontrasting
confidence: 98%
“…O tabaco aumenta o risco de infecção do sítio cirúrgico, retarda o processo de cicatrização e ainda tem a capacidade de aumentar as deiscências de sutura. Sendo essenciais orientações em relação à suspensão do fumo no período pré-operatório [12].…”
Section: Discussionunclassified
“…These data support manifold studies documenting unfavourable wound‐healing processes in smokers . Although not statistically significant in our population, it may be worth considering a strong recommendation of smoking cessation after upper eyelid surgery to promote a more satisfactory aesthetic outcome .…”
Section: Discussionmentioning
confidence: 99%